Skin in the game: Does paying for obesity treatment out of pocket lead to better outcomes compared to insurance coverage?. Issue 6 (June 2017) - Ard, Jamy D.; Emery, Matt; Cook, Miranda; Hale, Erica; Frain, Annette; Lewis, Kristina H.; Song, Eunyoung
Abstract : Objective: To determine whether insurance coverage for medical weight loss treatment was associated with different program engagement and weight loss outcomes compared to those who paid out of pocket. Methods: One‐year outcomes from an academic medical weight management program were used to compare two groups: employees ( n = 480) with insurance coverage ("covered") versus nonemployees ( n = 463) who paid out of pocket ("self‐pay"). Demographics and weight were abstracted from medical records. Socioeconomic status was estimated using neighborhood demographics. Group differences in weight were analyzed using generalized linear modeling adjusted for age, baseline BMI, sex, program type, and neighborhood socioeconomic status. Results: Covered patients were younger (46.5 ± 10.6 vs. 51.6 ± 12.5) with a lower BMI (38.5 ± 7.5 vs. 41.3 ± 9.9) compared to self‐pay ( P < 0.001). Self‐pay patients resided in higher annual per capita income neighborhoods (+4, 545, P < 0.001). Program dropout was lower for covered patients (12.7% vs. 17.6%, P = 0.03). There was no significant difference in 12‐month weight loss between groups in adjusted models; covered patients lost 13.4%, compared to 13.6% for self‐pay. Conclusions: Data from an academic medical weight management program suggest that individuals with access to insurance coverage for nonsurgical obesity treatment have lower levels of attrition and similar levels of participation and outcomes as those who pay out of pocket.